Hubungan Pola Asuh Orang Tua dengan Kecerdasan Emosional pada Perilaku Seksual Pranikah dan Perilaku Sosial di Kalangan Remaja - Nikmah, Islakhatun; Mardliyah, Sjafiatul (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
This study aims to explore the partial relationship between Parenting Patterns and Emotional Intelligence related to premarital sexual behavior and social behavior among adolescents. This study was conducted in Dusun Bareng, Banter Village, Gresik Regency. The approach and type of research used were quantitative descriptive with a correlational research type. The study population consisted of adolescents aged 12-21 years with a total of 25 people. Data were collected using questionnaires and interviews via Google Form and measured using a binary scale, then analyzed using IBM SPSS software version 25 with the Spearman Rank correlation analysis technique and a significance level of 0.05. The results showed that (1) the correlation coefficient value was greater than 0.05, namely 0.203> 0.05, then H0 was accepted and Ha was rejected. This means that there is no significant relationship between parenting patterns and emotional intelligence on premarital sexual behavior among adolescents. The correlation value is 0.548, which indicates a moderate and positive or unidirectional relationship. This means that the better the parenting pattern, the higher the emotional intelligence possessed by adolescents. (2) The correlation coefficient value is less than 0.05, namely 0.011 < 0.05, so Ha is accepted and H0 is rejected. This means that there is a significant relationship between parenting patterns and emotional intelligence related to social behavior among adolescents. The correlation value is 0.583, which indicates a moderate and positive or unidirectional relationship. This means that the better the parenting pattern, the higher the emotional intelligence possessed by adolescents.